2013
DOI: 10.1371/journal.pone.0070554
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Malignant Plasma Cell Proliferation by Eosinophils

Abstract: The biology of the malignant plasma cells (PCs) in multiple myeloma (MM) is highly influenced by the bone marrow (BM) microenvironment in which they reside. More specifically, BM stromal cells (SCs) are known to interact with MM cells to promote MM cell survival and proliferation. By contrast, it is unclear if innate immune cells within this same space also actively participate in the pathology of MM. Our study shows for the first time that eosinophils (Eos) can contribute to the biology of MM by enhancing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 38 publications
2
27
0
1
Order By: Relevance
“…Our prior work 14,20 and experiments in Figure 1 suggest that DC and MM cells themselves are important sources of CD80 and/or CD86. However, macrophages 19 and eosinophils 52 are also present in the MM microenvironment and express CD80/CD86. Nonhematopoietic stromal cells Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…Our prior work 14,20 and experiments in Figure 1 suggest that DC and MM cells themselves are important sources of CD80 and/or CD86. However, macrophages 19 and eosinophils 52 are also present in the MM microenvironment and express CD80/CD86. Nonhematopoietic stromal cells Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…(20) Slides were stained either with hematoxylin and eosin (H&E) or with immunofluorescence techniques using anti-CD19 antibody (Abcam, Cambridge, MA, USA) to detect B cells and anti-MBP antibody (EMD Millipore, Billerica, MA, USA) to detect Eos. Fluorescein-conjugated goat anti-rabbit Ig (Molecular Probes, Grand Island, NY, USA) and rhodamine-conjugated goat anti-mouse Ig (Chemicon International, Billerica, MA, USA) were used as secondary antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…We subsequently demonstrated that in the human PC malignancy, multiple myeloma, Eos within the tumor microenvironment can induce proliferation of the malignant cells thereby contributing to disease pathology. (20) Based on these findings, we questioned whether the proliferation-inducing effect of Eos on myeloma cells is a phenomenon that is restricted to this malignancy, or perhaps it is applicable to normal B-lineage cells as well. Indeed, via both transgenic mouse models and in vitro study of human Eos, we provide strong evidence that eosinophils do in fact impact the biology of normal B cells.…”
Section: Introductionmentioning
confidence: 99%
“…Eosinophils contribute to MM cells proliferation in a largely contact-independent manner, though not by IL-6 or APRIL, usually produced by many other kinds of BM cell types to support normal and malignant PC survival and proliferation [47]. …”
Section: Immunome: An Emerging Role In MM Microenvironmentmentioning
confidence: 99%